2016
DOI: 10.1111/add.13477
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption as a cause of cancer

Abstract: There is strong evidence that alcohol causes cancer at seven sites in the body and probably others. Current estimates suggest that alcohol-attributable cancers at these sites make up 5.8% of all cancer deaths world-wide. Confirmation of specific biological mechanisms by which alcohol increases the incidence of each type of cancer is not required to infer that alcohol is a cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(120 citation statements)
references
References 35 publications
1
110
1
8
Order By: Relevance
“…8,48 Recent findings do not support an overall protective effect from alcohol consumption. 18,50-52 Flawed study designs have been implicated in earlier findings of "protective effects" 53-58 -however, a great deal of controversy on this topic remains. 51,55,[59][60][61][62] A large proportion of participants in this study reported light-moderate drinking (0.1 to 29.9 g of ethanol/day or < 1 to 2 drinks/day), and may be unaware of the potential harm associated with even small Continued on the following page but regular amounts of alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,48 Recent findings do not support an overall protective effect from alcohol consumption. 18,50-52 Flawed study designs have been implicated in earlier findings of "protective effects" 53-58 -however, a great deal of controversy on this topic remains. 51,55,[59][60][61][62] A large proportion of participants in this study reported light-moderate drinking (0.1 to 29.9 g of ethanol/day or < 1 to 2 drinks/day), and may be unaware of the potential harm associated with even small Continued on the following page but regular amounts of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 However, recent evidence has challenged these findings and suggest that there is no safe limit of consumption, especially for cancer. [18][19][20][21] Despite the controversy, identifying a safe threshold based on sound methodology which accounts for beverage type, the frequency and volume of consumption and patterns of use for alcohol remains an important research question. 21 Recent reviews on the topic suggest that even light-to-moderate alcohol use may not be protective for chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence strongly suggests that moderate to heavy alcohol consumption increases the risk of cancer of the oral cavity, pharynx, larynx, esophagus, liver, colon, rectum and female breast [1][2][3]. Recent estimates indicate that the relative risk for heavy drinkers compared with nondrinkers and occasional drinkers is 5.13 for oral and pharyngeal cancer, 4.95 for esophageal 2 cancer, 2.65 for laryngeal cancer, 2.07 for liver cancer, 1.44 for colorectal cancer and 1.61 for breast cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 5.8% of cancer deaths world-wide are attributable to alcohol use [5]. However, the biological mechanism by which alcohol causes cancer is unclear [1,2,6,7]; this is often raised as an objection to accept the strong epidemiological link between alcohol consumption and cancer [2].…”
Section: Introductionmentioning
confidence: 99%
“…Connor makes a cogent argument for 'having it both ways' [1]. We agree that it is entirely plausible that alcohol causes cancer but does not afford drinkers a cardiovascular benefit.…”
mentioning
confidence: 94%